PETROELECTRICAL INVESTIGATION OF BOREHOLE CORE OF BLACK SEA SHELF - VYZHVA, S.; REVA, M.; HOZHYK, A.; ONYSHCHUK, V.; ONYSHCHUK, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2008)
The features of method and resuts of petroelectrical investigation of complex-structured terrigenous reservoir are considered. The results of determination of specific electric resistance and its connection with capasity properties of sandstones of one of Black Sea shelf drilling interval are discussed in this article.